Effects of Music Therapy on The Mood of Family-Caregivers and Care Staffs and Relationships between Mood and Healing Sense in a Palliative Care Ward - Michiyo, Ando (International Journal of Psychotherapy Practice and Research, 2017)
Objective: The present study examined effects of music therapy on mood and healing sense of family-caregivers and staffs in a palliative care ward and their relationships in order to elevate well-being. Method: This study is a cross-sectional study. Participants were 25 family caregivers and staffs related to patients in a palliative care ward in Japan. The professional Jazz pianist played piano at live concert once and the audience sang in one session. Participants completed the Japanese UWIST Mood Adjective Check List (JUMACLE) consisted of Tension Arousal (TA) and Energetic Arousal (EA) pre and post music therapy, the Healing questions, and comments of this therapy only post. Results: The TA score significantly decreased from 18.3 to 14.6 (p<0.05), and the EA score significantly increased from 32.1 to 35.1 (p<0.05). The mean healing questions scores was 4.5 point of total 5 point. The healing score significantly correlated with EA (r=.46, p<.05), but not with TA. Conclusion: The music therapy focused on Jazz music decreased tension or anxiety and increased vigor or energy, and healing sense related to vigor. Music therapy in a palliative care for family-caregivers and staffs may be useful to promote their well-being.
Keywords: music therapy; mood; tension arousal; energetic arousal; healing sense.